Highly stable CsPbBr3 quantum dots by silica-coating and ligand modification for white light-emitting diodes and visible light communication - Li, Xianwen; Cai, Wensi; Guan, Hongling; Zhao, Shuangyi; Cao, Siliang; Chen, Chen; Liu, Min; Zang, Zhigang (Chemical engineering journal (Lausanne, Switzerland : 1996), 2021)
•Silica coated DDAB-CsPbBr3 QDs exhibit better properties than regular CsPbBr3.•High performance warm WLEDs based on modified CsPbBr3 QDs are realized.•Visible light communication exhibits a typical low-pass frequency response. Owing to their superior optical and electronic properties, all inorganic metal halide CsPbX3 (X = Cl, Br, and I) perovskite quantum dots (QDs) are regarded as excellent candidates for various optoelectronic applications. However, the instability of such materials greatly hampers their practical applications. In this work, silica-coated didodecyldimethylammonium bromide (DDAB) capped CsPbBr3 QDs are prepared via a facile method at room temperature. The as-prepared DDAB-CsPbBr3/SiO2 QDs composites demonstrate an effectively improved photoluminescence quantum yield (PLQY) and stability against ethanol and heat. Moreover, the green DDAB-CsPbBr3/SiO2 QDs composites and red InAgZnS QDs are applied as color-converting layers on a blue LED chip for warm white light-emitting diodes (WLEDs). Such WLEDs exhibit an excellent luminescent performance with a color rendering index (CRI) of 88, a color coordinate of (0.41, 0.38), a correlated color temperature (CCT) of 3209 K, and a high power efficiency of 63.4 lm W−1. Besides, such WLEDs are used for visible light communication (VLC), exhibiting a typical low-pass frequency response, with a corresponding −3 dB bandwidth of about 1.5 MHz. By applying orthogonal frequency division multiplexing (OFDM) with a bit loading, a maximum achievable rate of the VLC system reaches 5.9 Mbps, which is almost four times of their measured −3 dB bandwidth. These results demonstrate the potential of prepared DDAB-CsPbBr3/SiO2 QDs composites not only in high-performance WLEDs, but also as an excitation light source to achieve VLC.